2017
DOI: 10.3748/wjg.v23.i23.4243
|View full text |Cite
|
Sign up to set email alerts
|

miR-382 functions as a tumor suppressor against esophageal squamous cell carcinoma

Abstract: AIMTo explore the effect of miR-382 on esophageal squamous cell carcinoma (ESCC) in vitro and its possible molecular mechanism.METHODSEca109 cells derived from human ESCC and Het-1A cells derived from human normal esophageal epithelium were used. Lentivirus-mediated miR-382 was overexpressed in Eca109 cells. The effect of miR-382 on cell proliferation was evaluated by MTT and colony formation assay. For cell cycle analysis, cells were fixed and stained for 30 min with propidium iodide (PI) staining buffer cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
5
16
0
Order By: Relevance
“…A clear understanding of the relationship between miRNA and the biological behaviour of malignant cells would render a novel index for early diagnosis, progress monitoring, and prognosis judgement . Previous studies have indicated that multiple members from miR‐382 family were implicated in the inhibition of malignancies, such as colorectal cancer, liver cancer, and esophageal squamous cell carcinoma . From a mechanistic point of view, miR‐382 impedes the progression of NSCLC by repressing SETD8 expression .…”
Section: Discussionmentioning
confidence: 99%
“…A clear understanding of the relationship between miRNA and the biological behaviour of malignant cells would render a novel index for early diagnosis, progress monitoring, and prognosis judgement . Previous studies have indicated that multiple members from miR‐382 family were implicated in the inhibition of malignancies, such as colorectal cancer, liver cancer, and esophageal squamous cell carcinoma . From a mechanistic point of view, miR‐382 impedes the progression of NSCLC by repressing SETD8 expression .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-382, a microRNAs in the chromosome 14q32 locus, has been shown to be involved in development, metastasis, and therapeutic resistance in multiple types of cancers. It functions as a tumor suppressor in colorectal cancer,8,9 ovarian cancer,10 esophageal squamous cell carcinoma,11,12 osteosarcoma,13,14 prostate cancer,15 melanoma,16 and non-small cell lung cancer 17. MiR-382 exhibits oncogenic properties in gastric cancer,18 hepatocellular carcinoma,19 and breast cancer 20.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, COUP-TFII is at the center of a miRNA network that elegantly explain the loss of EMT. MiR-382 is an onco-suppressor in non-small-cell lung, ovarian, prostate and esophageal cancers [189][190][191][192], and it is downregulated in colorectal cancer where it inhibits tumor metastasis, blocking SP1, and sensitizes cancer cells to chemotherapy [193,194]. Interestingly, COUP-TFII potentiates the action of SP1 in angiogenesis and development [92,94], recognizing SP1 response elements and miR-382 directly binds COUP-TFII 3 -UTR, knocking down the receptor, and hence downregulates two transcription factors that are demonstrated to synergize and induce EMT.…”
Section: The Gastrointestinal Cancers: Mostly An Oncogenementioning
confidence: 99%